Study on the sedimentary characteristics of braided fluvial fan<subtitle>Taking the Shan-2 Member of the Shanxi Formation with XQ gas storage in the Ordos Basin as an example</subtitle> - Jialin Fu; Jieming Wang; Chun Li; Shujuan Xu; Jinkai Wang; Jinliang Zhang; Jun Xie; Dali Yue (Journal of Taibah University for Science)
As a typical tight sandstone gas reservoir in the Ordos Basin, the second member of the Shanxi Formation in the XQ gas field in the Ordos Basin has had rich gas reservoirs and good development effects in the past. On the basis of previous studies, this paper brings new understanding to the sedimentary model of this area. Nine kinds of single lithofacies and seven kinds of lithofacies combinations are determined. Braided fluvial fan deposits in distributive fluvial systems likely developed in this area. The study area is part of the middle subfacies of this sedimentary facies, and five kinds of sedimentary microfacies environments developed. Finally, establishing sedimentary model based on sedimentary characteristics. The braided fluvial fan sedimentary model based on DFS is of great significance for deepening the understanding of terrestrial sedimentary systems and providing guidance for the exploration and development of oil and gas bearing basins.